Doped ruthenium dioxide catalyst as well as preparation method and application thereof
The doped ruthenium dioxide catalyst prepared by the template method constructs a core-shell structure and optimizes the electronic structure, which solves the structural and stability problems of ruthenium-based catalysts in high oxidation environments. It realizes the oxygen evolution activity and stability in acidic electrolytes, improves the oxygen evolution activity and stability of the catalyst in acidic electrolytes, solves the problems of structural collapse and dissolution and loss of active sites in existing technologies, and achieves high-efficiency electrochemical performance.
Patent Information
- Application Number
- CN202511068658.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-31
- Publication Date
- 2025-12-05
AI Technical Summary
Ruthenium-based catalysts are prone to over-oxidation in highly oxidizing environments, leading to the collapse of the catalyst crystal structure, dissolution and loss of active sites, and consequently a significant decline in catalytic performance.
Doped ruthenium dioxide catalysts were prepared using a template method. A precursor solution containing glucose and dopants was dropped onto high-temperature hard template nanoparticles to construct a core-shell structure, which was then calcined in stages to form a metal core-oxide shell structure. Combined with the synergistic effect of dopant elements, the electronic structure on the catalyst surface was optimized, the migration and aggregation of dopants were suppressed, and the exposure of active sites and the stability of electron supply were improved.
It significantly improves the oxygen evolution activity and stability of the catalyst, exhibits excellent electrochemical performance in acidic electrolytes, reduces overpotential, and can operate stably for a long time at high current densities, thereby reducing process costs.
Smart Images

Figure CN121065750A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of catalytic material preparation, and relates to a doped ruthenium dioxide catalyst and a preparation method and application thereof, in particular to a transition metal or non-metal element doped ruthenium dioxide catalyst and a preparation method and application thereof in an electrochemical oxygen evolution reaction. BACKGROUND
[0002] Under the background of global energy transformation, the development and utilization of renewable energy has become a global trend. The technology of hydrogen production by water electrolysis under acidic conditions is one of the key ways to reduce the world's dependence on fossil fuels and achieve sustainable energy development. However, due to the slow four-electron transfer process, the reaction kinetics in the acidic oxygen evolution reaction (OER) is very slow, which prompts people to find high-activity electrocatalysts to reduce the reaction barrier of OER.
[0003] For decades, iridium (Ir)-based materials and ruthenium (Ru)-based materials have been considered as benchmark electrocatalysts for achieving the best balance between stability and activity in acidic OER. However, Ir-based materials face challenges such as low mass activity, extremely low abundance on earth, and high cost, which limit their large-scale practical application. In contrast, Ru is a more cost-effective choice, with a cost of 1 / 10 of Ir, and usually exhibits higher intrinsic activity. However, Ru-based OER materials, especially RuO x , are usually unstable due to the excessive oxidation of Ru into soluble RuO4 at high OER voltage (>1.4V), which leads to the direct shedding of Ru active sites on the surface, resulting in a significant decrease in activity and stability. In theory, the acidic OER activity and stability of RuO2 are based on several contradictions of the conventional mechanism, namely the adsorbed species evolution mechanism (AEM) and the lattice oxygen oxidation mechanism (LOM). In AEM, due to the scaling relationship between the adsorption energies of OOH* and OH*, the overpotential is thermodynamically limited to 370mV, while the crystal structure of the catalyst remains unchanged in principle during OER, thereby having good stability. Although the lattice oxygen-mediated mechanism (LOM) can break this scaling relationship, the participation of lattice oxygen will produce oxygen vacancies, leading to the damage of the catalyst structure and reducing its stability. Therefore, it is still a major challenge to achieve a catalyst with high activity and high stability.
[0004] Prior art CN116905016A discloses a method for preparing manganese-doped ruthenium dioxide-coated ruthenium electrocatalyst and its application, relating to the field of electrocatalytic materials technology. This preparation method uses ruthenium trichloride solution and manganese acetylacetone as raw materials, and glucose as a reducing agent dissolved in a water-alcohol mixed solvent. The mixture is first hydrothermally treated, and then heated with potassium chloride. The manganese-doped ruthenium dioxide-coated ruthenium electrocatalyst prepared by this prior art exhibits excellent catalytic activity and high stability, and is expected to solve the problem of poor catalyst activity and stability in acidic media, and can be used as the anode in PEM electrolyzers of industrial hydrogen evolution devices.
[0005] However, the manganese doping in this technical solution relies solely on precursor mixing (manganese acetylacetonate + RuC3) without introducing a directional doping process. This leads to uneven distribution of manganese in the ruthenium dioxide lattice, with some areas agglomerated, affecting catalytic performance. Secondly, using an organic precursor involves multiple high-temperature treatments and repeated washing and drying steps, making the process complex. Summary of the Invention
[0006] The purpose of this invention is to provide a transition metal or nonmetal element-doped ruthenium dioxide catalyst and its preparation method, to solve a key problem faced by ruthenium-based catalysts in highly oxidizing environments: active Ru species are easily over-oxidized to generate high valence states. (n>4, such as soluble RuO4), which leads to the collapse of the catalyst crystal structure and the dissolution and loss of active sites, thereby causing a significant decrease in catalytic performance.
[0007] The objective of this invention can be achieved through the following technical solutions:
[0008] The first aspect of the present invention provides a method for preparing a doped ruthenium dioxide catalyst, comprising:
[0009] A solution containing glucose, dopant, and ruthenium source was dropped onto high-temperature hard template nanoparticles and dried to obtain a precursor; the precursor was calcined and roasted to obtain a doped ruthenium dioxide catalyst.
[0010] The dopant element in the dopant is selected from at least one of manganese, iron, cobalt, nickel, selenium, molybdenum or tungsten.
[0011] In some specific embodiments, the feeding ratio of glucose, dopant, ruthenium source, and hard template nanoparticles is (0.45-0.55)g:(0.07-0.09)mmol:(0.3-0.4)mmol:(7.5-8.5)g.
[0012] In some specific embodiments, the dopant is a water-soluble salt selected from at least one of manganese salt, iron salt, cobalt salt, nickel salt, selenium salt, tungsten salt, or molybdenum salt.
[0013] In some specific embodiments, the hard template is selected from at least one of NaCl, KCl or Na2SO4.
[0014] In some specific embodiments, the ruthenium source is a water-soluble ruthenium salt.
[0015] In some specific embodiments, the dopant and the ruthenium source are corresponding chloride salts, including manganese chloride and its hydrate, nickel chloride and its hydrate, iron chloride and its hydrate, cobalt chloride and its hydrate, tungsten hexachloride and its hydrate, molybdenum chloride and its hydrate, selenium chloride and its hydrate, ruthenium chloride and its hydrate.
[0016] In some specific embodiments, the method for preparing the hard template nanoparticles comprises: adding alcohol to the hard template aqueous solution to precipitate the hard template, and drying to obtain the hard template nanoparticles.
[0017] In some preferred embodiments, in the hard template aqueous solution, the feeding ratio of the hard template to water is 65-75 g: 180-220 mL; the alcohol is ethanol, which is added at a stirring speed of 100-1000 r / min.
[0018] In some specific embodiments, the temperature of the high-temperature hard template nanoparticles is 120-140℃.
[0019] In some specific embodiments, in the calcination, the calcination temperature is 300-850℃, the calcination time is 1.5-2h, the calcination atmosphere is nitrogen or inert gas, and the preferred heating rate is 8-10℃ / min.
[0020] In some specific embodiments, in the calcination, the calcination temperature is 300-450℃, the calcination time is 1-2h, the calcination atmosphere is air, and the preferred heating rate is 8-10℃ / min.
[0021] In some specific embodiments, before the calcination, water washing and drying are performed.
[0022] The second aspect of the present application provides a doped ruthenium dioxide catalyst prepared by the method as described above.
[0023] The third aspect of the present application provides an application of the doped ruthenium dioxide catalyst as described above, which comprises using the doped ruthenium dioxide catalyst as an OER catalyst for acidic electrolytic water.
[0024] Compared with the prior art, the present application has the following beneficial effects:
[0025] 1) Excellent oxygen evolution activity and stability: The present application provides a transition metal or non-metal element doped ruthenium dioxide catalyst and its preparation method and application. The catalyst is prepared by a template method strategy: using nanoparticles such as sodium chloride as a hard template, under mild oil bath conditions, dropwise adding a precursor solution containing glucose and a target doped element chloride salt, constructing a core-shell structure and synchronously realizing the doping of multiple elements (Mn, Ni, Fe, Co, W, Mo, Se), and the core-shell structure with metal as the core and oxide as the shell cooperates with the doping. Ru at the interface provides electrons during the reaction, and the internal gradually oxidizes, but the electron supply in the bulk phase does not cause a large fluctuation in the valence state of Ru, thereby solving the problem that active Ru species is easily over-oxidized to form high-valence state and further affecting the catalytic activity and stability. In addition, the segmented calcination process and high-temperature nitrogen environment promote atomic diffusion and migration, avoiding local enrichment, so that the obtained catalyst has excellent fine structure. The hard template nanopores provide a spatial confinement effect, inhibit the migration and aggregation of doped atoms, and are beneficial to improve the surface exposure degree of active sites and the contact area of the catalyst and the electrolyte. More importantly, the doped transition metal or rare earth element adjusts the local electronic structure of the catalyst surface, optimizes the adsorption energy of the active site to the oxygen-containing intermediate, effectively reduces the energy barrier of the reaction rate-limiting step, thereby significantly improving the catalytic activity. In the acidic electrolyte, it has excellent oxygen evolution activity and stability, the lowest overpotential reaches 200mv, and can stably operate at 100mA / cm 2 under high current density for 1000 hours, and has a wide application prospect in the field of water electrolysis;
[0026] 2) Low process cost: The present application uses an economic and efficient template method strategy for preparation, uses inexpensive inorganic salt (such as sodium chloride) as a hard template, and obtains nanoparticles by ethanol precipitation, and the template can be recycled multiple times, which significantly reduces the raw material cost. BRIEF DESCRIPTION OF DRAWINGS
[0027] Figure 1 XRD patterns of the catalysts prepared in Examples 1-8;
[0028] Figure 2 Scanning electron microscope images of the catalysts prepared in Example 6 and Example 8;
[0029] Figure 3 LSV curve graphs of the catalysts prepared in Examples 1-8 in the acidic (0.5M H2SO4) electrolyte OER;
[0030] Figure 4 Tafel curve slope graphs of the catalysts prepared in Example 6 and Example 8;
[0031] Figure 5The catalyst prepared for Example 6 and Example 8 was tested in acidic (0.5 M H2SO4) electrolyte at a current density of 100 mA cm -2 The long-term stability test results are shown below.
[0032] Figure 6 The catalyst prepared for Example 1 was tested in acidic (0.5 M H2SO4) electrolyte at a current density of 100 mA cm -2 The long-term stability test results are shown below.
[0033] Figure 7 High-resolution X-ray photoelectron spectroscopy (XPS) of Ru 3d in the catalyst prepared for Example 8. DETAILED DESCRIPTION
[0034] The application will be described in detail below with reference to the drawings and specific examples. The examples are implemented on the premise of the technical solution of the application, and detailed implementation and specific operation processes are given, but the protection scope of the application is not limited to the examples below.
[0035] In the following examples, unless otherwise specified, the raw reagents or processing techniques are all conventional commercially available products or conventional processing techniques in the art. The processing temperature is room temperature, the processing pressure is atmospheric pressure, and the processing atmosphere is air.
[0036] The evaluation criteria for water electrolysis oxygen evolution performance are as follows: electrochemical tests were carried out on an electrochemical workstation (Kost) using a three-electrode system at room temperature. The OER performance was measured in 0.5 M H2SO4 electrolyte, in which a Hg / Hg2SO4 electrode and a platinum sheet were used as the reference electrode and the counter electrode, respectively. 10 mg of electrocatalyst was dispersed in a mixed solution of 1 mL Nafion solution as an adhesive, and after ultrasonic treatment for 1 hour, an ink was obtained. The uniform ink was dropped on a 1 × 1 cm 2 carbon paper, and was fully air-dried at room temperature. The mass loading of the electrocatalyst on the carbon paper was controlled at about 0.4 mg cm -2 . The catalyst ink dropped on the carbon paper (1 × 1 cm 2 ) was used as the working electrode. All test potentials were converted to the potential values of the reversible hydrogen electrode (RHE).
[0037] Comparative Example
[0038] A RuO2 oxygen evolution catalyst, the preparation method thereof comprising:
[0039] NaCl nanoparticles were obtained by adding 70 g NaCl into 200 ml deionized water, stirring at room temperature (700 r / min), adding anhydrous ethanol while stirring until NaCl was completely precipitated, and drying at 60°C; 0.4 mmol RuCl3 was dissolved in 2 ml deionized water to prepare a precursor solution; 8.5 g NaCl nanoparticles were added dropwise into the precursor solution at 120°C, and the mixture was dried and ground to obtain a precursor; the obtained precursor was placed in a tube furnace and heated to 300°C at a heating rate of 10°C / min under a nitrogen atmosphere, and calcined for 2 h; the precursor was placed in a muffle furnace and heated to 400°C at a heating rate of 5°C / min under an air atmosphere, and calcined for 3 h; the obtained sample was dispersed in 200 ml deionized water, filtered and washed, and vacuum dried to obtain RuO2 nanoparticles.
[0040] Example 1
[0041] A Mn doped Ru@RuO2 oxygen evolution catalyst, the preparation method comprising:
[0042] NaCl nanoparticles were obtained by adding 70 g NaCl into 200 ml deionized water, stirring at room temperature (700 r / min), adding anhydrous ethanol while stirring until NaCl was completely precipitated, and drying at 60°C; 0.4 mmol RuCl3 was dissolved in 2 ml deionized water to prepare a precursor solution; 8.5 g NaCl nanoparticles were added dropwise into the precursor solution at 120°C, and the mixture was dried and ground to obtain a precursor; the obtained precursor was placed in a tube furnace and heated to 300°C at a heating rate of 10°C / min under a nitrogen atmosphere, and calcined for 2 h; the obtained sample was dispersed in 200 ml deionized water, filtered and washed, and vacuum dried to obtain RuO2 nanoparticles.
[0043] From Figure 6 It can be seen that the catalyst prepared in this example has excellent electrochemical activity and stability, and can run for 1000 h at a current density of 100 mA / cm2 in an acidic (0.5M H2SO4) electrolyte for long-term stability test. 2
[0044] Example 2
[0045] A Fe doped Ru@RuO2 oxygen evolution catalyst, the preparation method comprising:
[0046] 68 g NaCl was added into 200 ml deionized water, stirred at room temperature, the stirring speed was 800 r / min, ethanol was added while stirring until KCl completely precipitated, and KCl nanoparticles were obtained by drying at 80℃; 0.53 g glucose, 0.083 mmol FeCl3 and 0.36 mmol RuCl3 were dissolved in 2 ml deionized water to prepare a precursor solution; 8 g KCl nanoparticles were taken, and the precursor solution was added dropwise at 130℃, and then the precursor was obtained after drying and grinding; the obtained precursor was placed in a tube furnace, heated to 820℃ at a heating rate of 8℃ / min in a nitrogen atmosphere, and kept for 1.5 h; the obtained sample was dispersed in 200 ml deionized water, washed by suction filtration, and dried in vacuum to obtain the product, which was transferred to a muffle furnace, heated to 400℃ at a heating rate of 10℃ / min in an air atmosphere, and kept for 1.5 h to obtain a Fe doped Ru@RuO2 oxygen evolution catalyst.
[0047] From Figure 1 It can be seen that the crystal structure of the doped Ru@RuO2 core-shell structure in this embodiment has little effect, and the main effect may be reflected in the peak intensity and width, thereby affecting the surface properties or crystal defects of the material to improve the electrochemical activity. Figure 3 It can be seen that its electrochemical performance is much better than that of RuO2.
[0048] Example 3
[0049] A Co doped Ru@RuO2 oxygen evolution catalyst, the preparation method thereof comprises:
[0050] 66 g Na2SO4 was added into 200 ml deionized water, stirred at room temperature, the stirring speed was 900 r / min, ethanol was added while stirring until Na2SO4 completely precipitated, and Na2SO4 nanoparticles were obtained by drying at 60℃; 0.52 g glucose, 0.086 mmol CoCl2 and 0.35 mmol RuCl3 were dissolved in 2 ml deionized water to prepare a precursor solution; 7.9 g Na2SO4 nanoparticles were taken, and the precursor solution was added dropwise at 120℃, and then the precursor was obtained after drying and grinding; the obtained precursor was placed in a tube furnace, heated to 750℃ at a heating rate of 10℃ / min in a nitrogen atmosphere, and kept for 2 h; the obtained sample was dispersed in 200 ml deionized water, washed by suction filtration, and dried in vacuum to obtain the product, which was transferred to a muffle furnace, heated to 350℃ at a heating rate of 10℃ / min in an air atmosphere, and kept for 1.5 h to obtain a Co doped Ru@RuO2 oxygen evolution catalyst.
[0051] The catalyst prepared in this embodiment has a core-shell structure, a sheet layer morphology, and excellent electrochemical activity and stability.
[0052] Example 4
[0053] A Ni doped Ru@RuO2oxygen evolution catalyst, the preparation method comprising:
[0054] 70 g of NaCl was added to 200 ml of deionized water, stirred at room temperature, the stirring speed was 800 r / min, and ethanol was added while stirring until the NaCl was completely precipitated, and the NaCl nanoparticles were obtained by drying at 60°C; 0.5 g of glucose, 0.085 mmol of NiCl2and 0.35 mmol of RuCl3were dissolved in 2 ml of deionized water to prepare a precursor solution; 8.5 g of NaCl nanoparticles were taken, and the precursor solution was added dropwise at 120°C, and the precursor was obtained after drying and grinding; the obtained precursor was placed in a tube furnace, heated to 800°C at a heating rate of 8°C / min in a nitrogen atmosphere, and heat-treated for 2 h; the obtained sample was dispersed in 200 ml of deionized water, and the product was obtained after vacuum drying by suction filtration and washing; the product was transferred to a muffle furnace, heated to 300°C at a heating rate of 8°C / min in an air atmosphere, and heat-treated for 2 h to obtain a Ni doped Ru@RuO2oxygen evolution catalyst.
[0055] The catalyst prepared in this example has a core-shell structure, a sheet layer structure, and good electrochemical activity and stability.
[0056] Example 5
[0057] A Se doped Ru@RuO2oxygen evolution catalyst, the preparation method comprising:
[0058] 70 g of NaCl was added to 200 ml of deionized water, stirred at room temperature, the stirring speed was 700 r / min, and ethanol was added while stirring until the NaCl was completely precipitated, and the NaCl nanoparticles were obtained by drying at 60°C; 0.5 g of glucose, 0.085 mmol of SeCl2and 0.4 mmol of RuCl3were dissolved in 2 ml of deionized water to prepare a precursor solution; 8.5 g of NaCl nanoparticles were taken, and the precursor solution was added dropwise at 120°C, and the precursor was obtained after drying and grinding; the obtained precursor was placed in a tube furnace, heated to 850°C at a heating rate of 8°C / min in a nitrogen atmosphere, and heat-treated for 2 h; the obtained sample was dispersed in 200 ml of deionized water, and the product was obtained after vacuum drying by suction filtration and washing; the product was transferred to a muffle furnace, heated to 450°C at a heating rate of 10°C / min in an air atmosphere, and heat-treated for 2 h to obtain a Se doped Ru@RuO2oxygen evolution catalyst.
[0059] From Figure 1 and Figure 3It can be seen that the catalyst prepared in the embodiment has a core-shell structure, and has good electrochemical activity and stability.
[0060] Example 6
[0061] A Ru@RuO2oxygen evolution catalyst, a preparation method thereof comprises the following steps:
[0062] 70g of Na2SO4 was added to 200ml of deionized water, and stirred at room temperature at a stirring speed of 400r / min. Ethanol was added while stirring until the Na2SO4 was completely precipitated. The Na2SO4 nanoparticles were obtained by drying at 60℃. 0.5g of glucose and 0.33mmol of RuCl3 were dissolved in 2ml of deionized water to prepare a precursor solution. 8.5g of Na2SO4 nanoparticles were taken, and the precursor solution was added dropwise at 120℃. After drying and grinding, the precursor was obtained. The obtained precursor was placed in a tube furnace and heated to 800℃ at a heating rate of 8℃ / min in a nitrogen atmosphere, and heat-treated for 2h. The obtained sample was dispersed in 200ml of deionized water, and was washed by suction filtration and vacuum dried to obtain the product. The product was transferred to a muffle furnace and heated to 450℃ at a heating rate of 10℃ / min in an air atmosphere, and heat-treated for 2h to obtain the Ru@RuO2oxygen evolution catalyst.
[0063] From Figure 1 It can be seen that the catalyst in the embodiment has a core-shell structure and a small size. From Figure 2 It can be seen that the material has a two-dimensional sheet structure. From Figure 3 It can be seen that the catalyst has good electrochemical activity. From Figure 5 It can be seen that the catalyst can be stably operated for more than 100h at a current density of 100mA / cm 2
[0064] Example 7
[0065] A W doped Ru@RuO2oxygen evolution catalyst, a preparation method thereof comprises the following steps:
[0066] The 70 g NaCl was added to 200 ml deionized water, stirred at room temperature, the stirring speed was 500 r / min, and ethanol was added while stirring until KCl was completely precipitated, and KCl nanoparticles were obtained by drying at 60°C; 0.45 g of glucose, 0.085 mmol of WCl2 and 0.36 mmol of RuCl3 were dissolved in 2 ml of deionized water to prepare a precursor solution; 8.5 g of KCl nanoparticles were taken, and the precursor solution was added dropwise at 120°C, and after drying, grinding was performed to obtain a precursor; the obtained precursor was placed in a tube furnace, heated to 750°C at a heating rate of 8°C / min in a nitrogen atmosphere, and calcined for 1.5 h; the obtained sample was dispersed in 200 ml of deionized water, and after washing by suction filtration and vacuum drying, the product was obtained, which was transferred to a muffle furnace, heated to 450°C at a heating rate of 10°C / min in an air atmosphere, and calcined for 2 h to obtain a W-doped Ru@RuO2 oxygen evolution catalyst.
[0067] Example 8
[0068] A Mo-doped Ru@RuO2 oxygen evolution catalyst, the preparation method thereof comprises the following steps:
[0069] The 70 g NaCl was added to 200 ml deionized water, stirred at room temperature, the stirring speed was 800 r / min, and ethanol was added while stirring until NaCl was completely precipitated, and NaCl nanoparticles were obtained by drying at 60°C; 0.5 g of glucose, 0.085 mmol of MoCl2 and 0.34 mmol of RuCl3 were dissolved in 2 ml of deionized water to prepare a precursor solution; 8.5 g of NaCl nanoparticles were taken, and the precursor solution was added dropwise at 120°C, and after drying, grinding was performed to obtain a precursor; the obtained precursor was placed in a tube furnace, heated to 800°C at a heating rate of 10°C / min in a nitrogen atmosphere, and calcined for 2 h; the obtained sample was dispersed in 200 ml of deionized water, and after washing by suction filtration and vacuum drying, the product was obtained, which was transferred to a muffle furnace, heated to 400°C at a heating rate of 10°C / min in an air atmosphere, and calcined for 1.5 h to obtain a Mo-doped Ru@RuO2 oxygen evolution catalyst.
[0070] Example 9
[0071] A Mo-doped Ru@MoRuO2 oxygen evolution catalyst, the preparation method thereof is only different from that of Example 8 in that equal mass of KCl is used instead of NaCl, and the rest is the same as Example 8.
[0072] Example 10
[0073] A Mo doped Ru@MoRuO2 oxygen evolution catalyst, the preparation method thereof is only different from that of Example 8 in that equal mass of Na2SO4 is used instead of NaCl, and the rest is the same as in Example 8.
[0074] Example 8 is the optimal scheme among all examples, and has the most excellent electrocatalytic oxygen evolution performance compared with other schemes, Figures 3-5 The relevant data results reflect the excellence of its performance. Specifically, from Figure 3 It can be seen that, when the current density is 10 mA cm -2 , the catalyst of Example 8 has the lowest overpotential of 200 mv compared with other examples, which reflects the outstanding electrocatalytic oxygen evolution performance. The electrochemical performance of the catalysts obtained from Example 9 and Example 10 is basically similar to that of Example 8, and at a current density of 10 mA cm -2 , the overpotential thereof is 190-210 mv, and at a current density of 100 mA cm -2 , it can also be stably operated for 100 h. Secondly, from Figure 4 It can be seen that the material of Example 8 has the lowest Tafel slope, which proves that the material has the best reaction kinetic rate in the electrocatalytic process. Figure 5 It can be observed that the potential of RuO2 gradually increases with time, indicating that its stability at this current density is poor. In contrast, the potential change of the catalysts prepared in Example 6 and Example 8 is small, showing better electrochemical stability. Among them, Example 8 has the lowest potential, and can be operated for 100 h in a long time test, indicating that the doping of Mo effectively improves the electrochemical performance and stability of the material. Finally, from Figure 7 It can be seen that, in the Ru@Mo 0.2 Ru 0.8 O2 catalyst, the chemical state of Ru changes correspondingly before and after the reaction, but high-valence Ru species are not generated. The reason is that in the reaction process, Ru at the interface position can provide electrons, while its interior is gradually oxidized, but oxidation is difficult to occur at the interface. In addition, there is also a case of electron transfer from Ru site to Mo site in the process, which makes the valence state of Ru rise. However, due to the existence of a large number of electron transport in the bulk phase of the catalyst, sufficient electron supply in the bulk phase can effectively maintain the relative stability of the valence state of Ru, avoiding large fluctuations thereof. It is the synergistic effect of the above factors that eventually makes the catalyst significantly improve in activity and stability.
[0075] These results show that the performance of the electrocatalyst can be significantly improved by the core-shell structure and doping strategy.
[0076] The embodiments described with reference to the drawings are exemplary and are intended to serve for the explanation of the present application and are not to be understood as a restriction of the present application. The embodiments are not to be regarded as a restriction of the present application, but any improvement made on the basis of the spirit of the present application is to be within the scope of protection of the present application.
[0077] The above description of the embodiments has been given by way of non-limiting examples so that those with ordinary skill in the art can understand and use the present application. It will be apparent to a person skilled in the art that various modifications can be made to the embodiments and that the general principles defined herein can be applied to other embodiments without inventive labor. Therefore, the present application is not limited to the above-described embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present application without departing from the scope of the present application should be within the scope of protection of the present application.
Claims
1. A method for preparing a doped ruthenium dioxide catalyst, characterized by, The application relates to a method for preparing a doped ruthenium dioxide catalyst. A solution containing glucose, a dopant and a ruthenium source is added dropwise to high-temperature hard-template nanoparticles, and a precursor is obtained by drying; The precursor is calcined and roasted to obtain the doped ruthenium dioxide catalyst. The doping element in the dopant is at least one selected from manganese, iron, cobalt, nickel, selenium, molybdenum or tungsten.
2. The method for preparing a doped ruthenium dioxide catalyst according to claim 1, characterized by, The feeding ratio of the glucose, the dopant, the ruthenium source and the hard-template nanoparticles is (0.45-0.55) g:(0.07-0.09) mmol:(0.3-0.4) mmol:(7-10) g.
3. The method of claim 1, wherein the method is characterized by: The dopant is a water-soluble salt, and is at least one selected from manganese salt, iron salt, cobalt salt, nickel salt, selenium salt, tungsten salt or molybdenum salt. The hard template is at least one selected from NaCl, KCl or Na2SO4.
4. The method of claim 1, wherein the method is characterized by: The ruthenium source is a water-soluble ruthenium salt.
5. The method of claim 1, wherein the method is characterized by: The preparation method of the hard-template nanoparticles comprises the following steps: adding alcohol into a hard-template aqueous solution to make the hard template precipitate, and drying to obtain the hard-template nanoparticles.
6. The method of claim 1, wherein the method is characterized by: The temperature of the high-temperature hard-template nanoparticles is 120-140 DEG C.
7. The method of claim 1, wherein the method is characterized by: In the calcination, the calcination temperature is 300-850 DEG C, the calcination time is 1.5-2 h, and the calcination atmosphere is nitrogen or inert gas.
8. The method of claim 1, wherein the method is characterized by: In the roasting, the roasting temperature is 300-450 DEG C, the roasting time is 1-2 h, and the roasting atmosphere is air.
9. A doped ruthenium dioxide catalyst, characterized by, The doped ruthenium dioxide catalyst is used as an OER catalyst for acid electrolytic water.
10. Use of a doped ruthenium dioxide catalyst according to claim 9, characterized in that The doped ruthenium dioxide catalyst is used as an OER catalyst for acid electrolytic water.
Citation Information
Patent Citations
Preparation method and application of manganese-doped ruthenium dioxide coated ruthenium electrocatalyst
CN116905016A